Another woman [videorecording (DVD)] - Allen, Woody, 1935-; Buckley, Betty; Danner, Blythe; Dennis, Sandy, 1937-1992; Farrow, Mia, 1945-; Hackman, Gene; Holm, Ian, 1931-2020; Houseman, John, 1902-1988; Plimpton, Martha, 1970-; Rowlands, Gena (Contemporary classics (Culver City, Calif.), 2001)
When a distinguished philosophy professor turns 50, she feels compelled to take emotional stock of her life. But the deeper she digs the more her life seems to unravel, until she realizes that her search for truth is a personal odyssey of self-examination, discovery and acceptance.